Educating for peace - Miśra, Lokanātha (Cambridge Scholars Pub., 2013)
We know that peace education helps individuals transform conflict in their own lives, understand and respect other cultures and ways of living, and treasure the Earth. Teachers of peace education encourage their students to cooperate with each other, think critically, solve problems constructively, take part in responsible decision-making, communicate clearly, and share their feelings and commitment openly. This book is written mainly for researchers, peace educators and students.